Study the Serum IL-6 Level between Rheumatoid Arthritis Patients and Control - Semaa Abdulrahman Shaban (Tikrit Journal of Pure Science)
This study involved (50) patient’s that complaining rheumatoid arthritis from both genders (7 females and 43 males). Their ages range from (26-68) years there are taken from hospitals and clinics, in addition to the control which involve (30) person that look normal and their ages ranges from (23-54).